2015
DOI: 10.5539/ass.v12n1p17
|View full text |Cite
|
Sign up to set email alerts
|

Examining Physical Activity and Play Behavior Preferences between First Graders and Last Graders in Primary School Children in Tehran

Abstract: School grounds are critical places because they are some of the few play areas available for children to develop and transfer peer culture. Moreover, school playtime, which is often called "recess", offers children daily opportunities for physical activity in the outdoor environment. During school years, age has always been presented in the studies on children as a fundamental component of their development. Children of different ages are interested in different play styles and have various play priorities. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There are several studies that have shown that children's game choices are affected by different variables (Kinzie & Joseph, 2008;Kuhaneck, Spitzer & Miller, 2010). Some of these studies found that game preferences of children vary across age and across newly developed skills (Christoph, Dorothée, Peter, 2009;Marouf, Che-Ani & Tawil, 2015;Quaiser-Pohl, Geiser, Lehmann, 2006). Another variable that affects game preferences of children is gender, although the underlying reasons cannot be explained clearly (Inal & Cagiltay, 2005;.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…There are several studies that have shown that children's game choices are affected by different variables (Kinzie & Joseph, 2008;Kuhaneck, Spitzer & Miller, 2010). Some of these studies found that game preferences of children vary across age and across newly developed skills (Christoph, Dorothée, Peter, 2009;Marouf, Che-Ani & Tawil, 2015;Quaiser-Pohl, Geiser, Lehmann, 2006). Another variable that affects game preferences of children is gender, although the underlying reasons cannot be explained clearly (Inal & Cagiltay, 2005;.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Bazdis (2008) states that learning through play is the most appropriate curricular approach for children because this approach relates to the natural characteristics of children who enjoyed playing. Hence, the implementation of this approach should take into account the needs and interests of students where teachers guide and support their students during the play activities (Marouf, Che-Ani, & Tawil, 2015). (Piaget, 1962).…”
Section: Free "Play" and Learningmentioning
confidence: 99%
“…It is stated that learning through play is the best method as it is linked to the natural characteristics of children who enjoy playing. As a result, the implementation of this method should take into account preschoolers' needs and interests, and educators should guide and support their preschoolers' play activities (Marouf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%